2019
DOI: 10.1002/brb3.1521
|View full text |Cite
|
Sign up to set email alerts
|

Retinal sublayer defect is independently associated with the severity of hypertensive white matter hyperintensity

Abstract: Purpose:To investigate the association of specific retinal sublayer thicknesses on optical coherence tomography (OCT) imaging with brain magnetic resonance imaging (MRI) markers using the Fazekas scale in hypertensive white matter hyperintensity (WMH) subjects.Methods: Eighty-eight participants (32 healthy controls and 56 hypertensive white matter hyperintensity subjects) underwent retinal imaging using the OCT and MRI.A custom-built algorithm was used to measure the thicknesses of the retinal nerve fiber laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(36 reference statements)
2
6
1
Order By: Relevance
“…Interestingly, the INL+HFL contains bundles of unmyelinated cone and rod photoreceptor axons (Lujan et al, 2011 ), whereas the OS is equivalent to the dendritic part of a photoreceptor cell. The decrease of the thickness of these two layers is consistent with the findings of a prior study of ganglion cells, in which the sublayer of axons and dendrites became thinner (Qu et al, 2020 ). This provides new evidence for a correlation between the neurites of retinal cells and white matter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the INL+HFL contains bundles of unmyelinated cone and rod photoreceptor axons (Lujan et al, 2011 ), whereas the OS is equivalent to the dendritic part of a photoreceptor cell. The decrease of the thickness of these two layers is consistent with the findings of a prior study of ganglion cells, in which the sublayer of axons and dendrites became thinner (Qu et al, 2020 ). This provides new evidence for a correlation between the neurites of retinal cells and white matter.…”
Section: Discussionsupporting
confidence: 91%
“…The GCL is composed of cell bodies, and it is more likely to be related to gray matter (Mutlu et al, 2017). Qu et al (2020) has also recently reported that the thickness of the NFL and GCL+IPL were associated with WMH, and deteriorate with the severity of lesions.…”
Section: White Matter Hyperintensities and The Onl+hfl/os Layer Of The Retinamentioning
confidence: 96%
“…Therefore the RNFL represents the direct neuroretinal contributions to the central nervous system and has been shown to correlate with cerebral white matter atrophy in neurodegenerative disease. [24][25][26][27] Kochunov et al 28,29 and others recently characterized white matter abnormalities as an underlying neural mechanism in schizophrenia. [30][31][32] Therefore preferential axonal loss in SSD might be related to similar white matter abnormalities evidenced in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of pRNFL damage was associated with the occurrence of MRI white matter lesions, hypertension, older age, and male sex. In another study, the authors investigated the thickness of retinal layers in patients with NSWMLs and healthy controls [53]. Thicknesses of the mRNFL and the GCIPL were significantly reduced in NSWMLs patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%